PENGELOLAAN ALOKSI DANA DESA DI KAMPUNG BUMI MAS, KECAMATAN SEPUTIH AGUNG, KABUPATEN LAMPUNG TENGAH DALAM PERSPEKTIF AKUNTABILITAS - Meri Susanti; Wahyu Widodo (P3M STISIPOL Dharma Wacana Metro, 2018)
The ability of the village apparatus in managing funds greatly determines the success of the use of village fund allocations in accordance with the objectives of community empowerment prioritized by the government through the Village Fund Allocation (ADD). This paper aims to describe accountability in terms of planning, implementation and accountability. The conclusion of this study is that at the planning stage the application of the principle of participatory, responsive, transparent; at the stage of implementing the principle of participatory, responsive, transparent; human resource competency factor.